Development of Two UWB Multiband MIMO Antennas with Enhanced Isolation and Cross-Correlation - Sarade, Shrenik; Ruikar, Sachin (Engineering, Technology & Applied Science Research, 2023)
An Ultra-Wide Band (UWB) MIMO antenna working at millimeter-wave is proposed in this research. It is composed of eight radiating elements with various shapes. It is designed with a rectangular structure and various carved slots. The carved slots are used to increase the antenna’s bandwidth. The antenna’s radiating elements are placed near one another, and thus, isolation is widespread. In order to improve the isolation of the MIMO antenna, parasitic elements and a defective ground structure are used. Antenna parameters such as Correlation Coefficient (CC), Envelope Correlation Coefficient (ECC), Diversity Gain (DG), and Total Active Reflection Coefficient (TARC) depend on the isolation. Parasitic elements with a rectangular form are positioned between the radiating patches. Rectangular-shaped ground structures with defects comprise the ground plane. An FR-4 substrate is used to fabricate the antenna. The analysis of the antenna shows that there is less than -14dB return loss, less than -40dB isolation, less than 0.0010 cross-correlation, less than 0.10 TARC, and higher than 500MHz bandwidth. The antenna uses a fractional bandwidth higher than 35% (UWB) for the 6GHz frequency and operates on a variety of bands. This antenna is suitable for many different wireless system applications.